Rare breast cancer: 246 invasive secretory carcinomas from the National Cancer Data Base. Issue 7 (4th April 2016) - Jacob, John Doromal; Hodge, Caitlin; Franko, Jan; Pezzi, Christopher M.; Goldman, Charles D.; Klimberg, Vicki Suzanne
Abstract : Background and Objectives: Invasive secretory breast carcinoma (SBC) is a rare subtype of breast malignancy. Methods: Cases of SBC and infiltrating ductal carcinoma (IDC) from the National Cancer Database (1998–2011) were queried. Results: Patients with SBC (n = 246) and IDC were identified (n = 1, 564, 068). The group with SBC was younger (age 56.4 ± 16.0 vs. 60.4 ± 13.9 years, P < 0.001), had similar tumor size (19.9 ± 17.8 vs. 21.6 ± 25.5 mm, P = 0.297), more frequently African‐Americans (24.1 vs. 14.8 vs. 13.7; P = 0.004), more well‐differentiated (32 vs. 18%, P < 0.001) and less likely to be hormone receptor positive (ER: 64 vs. 76%, P = 0.001; PR: 43 vs. 65%, P < 0.001). No differences were found for incidence of node‐positivity (32 vs. 34%, P = 0.520) and stage IV presentation (2.4 vs. 3.6%, P = 0.372). Breast conserving surgery (60 vs. 58%, P = 0.405) and hormonal therapy (67 vs. 71%, P = 0.489) rates were similar. Systemic chemotherapy was used less often for SBC (38 vs. 45%, P = 0.035). The overall survival of all patients with SBC was better than all patients with IDC (median not reached vs. 14.8 years, P = 0.025). Conclusion: SBC is an uncommon tumor that is often well‐differentiated and seen in younger women. Contrary to prior reports, they are frequently hormone receptor‐positive. Compared to IDC, overall survival is improved. J. Surg. Oncol. 2016;113:721–725 . © 2016 Wiley Periodicals, Inc.